Study on the Force Analysis of RV Transmission Mechanism - Xiaofen Ye; Min Zhu; Xinwen Chen; Yongshuai Meng; Feng Gong (Jixie chuandong)
A method for force analysis of RV transmission mechanism is proposed. The force analysis model of input shaft, planetary wheel, cycloidal wheel, needle tooth shell, crank shaft and planetary frame is established. Considering tangential force, radial force and gravity, the force of RV transmission mechanism is completely expressed in vector form. Based on VB.NET，an force analysis program of RV transmission is developed，which can quickly and accurately calculate the real time change of each force under different crank angle.